KARANGGENENG MAKMUR MICRO, SMALL, AND MEDIUM ENTERPRISES (MSME) SERVICES MARKETING STRATEGY TO IMPROVE THE ECONOMY OF VILLAGE COMMUNITIES - Sunyoto, Danang; Mulyono, Agus; Yoyce Ogwu, Ibukun (EMPOWERING HUMANITY, 2024)
To develop a marketing strategy for Micro, Small, and Medium Enterprises (MSMEs) in Karanggeneng Makmur Village, Sendangadi, Mlati, Sleman, and Yogyakarta using the SWOT analysis method. The village has great MSME potential but still faces various challenges in marketing its products and services, which have an impact on the economic growth of the village community as a whole. The SWOT method is used to identify the strengths, weaknesses, opportunities, and threats faced by MSMEs in the village in terms of marketing their services. Analysis results shows that MSMEs have a unique diversity of products and services, but face limited market access and a lack of knowledge about effective marketing strategies. However, there are opportunities to exploit potential markets around the village and support from local governments and non-governmental organizations. Based on the results of the analysis, an innovative and sustainable marketing strategy was developed to increase market access and income for MSMEs, which is expected to contribute to improving the economy of the village community as a whole. It is hoped that the results of this research can provide useful insights for the development of MSMEs and local economic development in rural areas.